Nitric oxide synthase in the brain of a teleost - Holmqvist, Bo I.; Östholm, Thomas; Alm, Per; Ekström, Peter (Neuroscience Letters, 1994)
The presence and distribution of the nitric oxide (NO) converting enzyme, NO synthase (NOS), was investigated in the brain of a teleost, the Atlantic salmon. Both NOS immunoreactive and NADPH diaphorase positive, non-neuronal and neuronal cell bodies, fibers and putative nerve terminals were identified throughout the brain. Even so, the staining was not identical in all regions. NO, synthesized by NOS-like enzymes, may play an important role in a diversity of cellular mechanisms in the brain of the salmon, including in neural systems related to olfactory, visual, hypophysiotrophic, viscero-sensoric and motor functions.